?STUDIES WITH POLYFUNCTIONALLY SUBSTITUTED HETEROAROMATIC COMPOUNDS: SYNTHESIS OF SOME NEW POLYFUNCTION,ALLY SUBSTITUTED PYRIDO [3, 2-c]- PYRIDINES ANDPYRIDO [2,3-C]-PYRIDAZINES (Biological Sciences - PJSIR, 1998)
The phenylhydrazino derivatives of ethyl acetoacetate (1), acetyl acetonitrile (11) and acetylacetone (17) reacted with malononitrile, malononitrile dimer (4a) or ethyl cyan acetate dimer (4b). The products were treated with benzaldehyde to yield different polyfunctionally substituted pyridopyridines and pyridopyri- dazines.